1903 Kan. Sess. Laws 548 - (:unkn) unknown (My University, 1903)
Relating to the Organization, Government, etc., of the State Militia, Ch. 359, § 3: No armed military force from another state or territory shall be permitted to enter the state without his permission, unless such military force is a part of the United States army or is acting under the authority of the United States. No independent military organization, except it is [sic] a corps of cadets at an educational institution, shall be permitted to bear arms without first securing permission from the commander-in-chief.
Keywords: MILITIAS